Carbon capture by ionic liquids - Khan, Huma Warsi; Yusuf, Mohammad; Elgharbawy, Amal A.M.; Makarem, Mohammad Amin; Maysore, Karuna (Elsevier, 2023)
The harmful impact of global warming on the environment caused by the production of greenhouse gases (GHGs) is of concern. Carbon dioxide is one of the main emerging gases from industries among GHGs. Convention carbon capture methods employ conventional solvents that are toxic and hazardous. Green processes employing greener solvents must be designed to protect the environment. Ionic liquids (ILs), a class of greener solvents can be employed to capture carbon dioxide because of their excellent characteristics. This chapter presents various processes employing ILs for the capture of carbon dioxide. ILs are being employed as adsorbent, absorbent, carrier, and extractant. This latter part of this chapter highlights the use of some predictive methods based on thermodynamic properties for selecting ILs for carbon capture. Moreover, this chapter proposes the prospects, challenges, and future research directions for employing ILs for carbon capture.